Menggali Potensi Bisnis Melalui Platform Media Sosial Pada Siswa SMA Negeri 3 Bengkulu Utara - Edy Hermansyah; Siswanto Siswanto; Yupianti Yupianti; Wahyu Hidayat; Fhariska Dhia Putri (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The rapid development of information technology, particularly social media, has significantly influenced business and digital marketing practices. This community service activity aims to improve the knowledge and skills of students at SMA Negeri 3 Bengkulu Utara in utilizing social media to explore business opportunities. The implementation methods included socialization, training, and mentoring for 30 twelfth-grade science students. The activity was conducted on November 16, 2024, using a semi-workshop approach. The results indicate an increase in students' understanding of social media utilization for entrepreneurship and a growing interest in starting digital-based businesses. The participants’ enthusiasm during the activity served as a key indicator of success. Therefore, this program is expected to encourage the emergence of creative, innovative, and technology-adaptive young entrepreneurs.